Writing Aphrodite: Imagining a Rhetoric of Desire for a Feminist Writing Course - Hildy Miller (Journal of the Assembly for Expanded Perspectives on Learning, 2006)
Reaching back to the post-Jungian goddess feminism of decades past, this essay shows how the mythical figure Aphrodite can serve as an image for an alternative rhetoric of desire in a contemporary feminist writing class.